Testing for home team and favorite biases in the Australian rules football fixed odds and point spread betting markets - Adi Schnytzer; Guy Weinberg (Bar-Ilan University, Department of Economics, 2007)
In this paper, we test two different kinds of bias; the favorite-longshot/favorite-underdog and the home team bias, and distinguish between the two, using a distinctive feature of the Australian Football League (AFL), that many games are played on neutral grounds. This is the first empirical study, to the best of our knowledge, to make a clear distinction between the two types of bias. We conduct our tests by subjecting 2001-2004 data for the AFL to detailed scrutiny, using standard econometric weak-form efficiency models of point spread and fixed odds betting markets. Where the results suggest the presence of a bias, we test potential profitability via betting simulation. We are able to reject the existence of any significant pure favorite-longshot/favorite-underdog bias in either market, and to demonstrate the existence of a significant bias in favor of teams with an apparent home ground advantage in games played outside Victoria in the point spread market and in the fixed odds market during 2002, 2004 and the period as a whole. Games in Melbourne and in Geelong are free of such a bias (except for 2003 in the point spread market in Geelong). Betting simulations which attempt to exploit these inefficiencies yield modest profits.
Keywords: 330; market efficiency; betting markets; sports economics; Australian Rules football; Fußballsport; Professioneller Sport; Glücksspiel; Prognoseverfahren; Bias; Australien